Kajian Histopatologi Serangan Pratylenchus spp. pada Akar Pisang Kultivar Kepok - Siwi Indarti; Bambang Rahayu TP (Universitas Gadjah Mada, 1998)
The root lesion nematode, Pratylenchus spp., were found infecting banana. The objective of this study was to investigate the damage and malformation on root tissues caused by these nematodes. The nematode inoculum was collected from roots of cultivar Kepok contained high population of Pratylenchus spp. Banana cv. Kepok were inoculated with 1000 nematodes as inoculum level per plant per pot for histopathological study. Pratylenchus spp. infected the root of Banana cv. Kepok and caused black necrotic lesions on the root surface. The exoderm, epiderm, and cortical tissue of the roots showed severe damage with necrotic cells or lesion. Especially on the cortex the burrowings were observed.